The Kansas Teacher Education Advocate, where we have been and where we could go - Stu Ervay (The Advocate, 2017)
Editorial. ORIGINS:​ The Advocate was begun in the 1970s by ATE-K Executive Director and past President Stu Ervay, who initially intended it to be similar to the Phi Delta Kappan in terms of format and content. The Kappan included articles that stimulated innovative thinking and possible action in America’s schools. The Advocate was meant to do the same thing for Kansas’ teacher education.